Voltage drop comparison in Lead-acid and Lithium-ion batteries on electric scooters - Sapteka, Anak Agung Ngurah Gde; Narottama, Anak Agung Ngurah Made; Widyatmika, Komang Agus (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2024)
This article compares the voltage drop on Lead-acid and Lithium-ion batteries used as an energy source for electric scooters. An experiment was conducted with five electric scooter users weighing 60.25 Kg, 70.60 Kg, 83.20 Kg, 95.40 Kg, and 103.75 kg to obtain data on voltage drop. Each user of this electric scooter carried out three experiments by circling about 1.07 Km at the Politeknik Negeri Bali area. This study proves that the voltage drop on the Lead-acid and Lithium-Ion batteries has a linear relationship to the weight of an electric scooter user with a 36V 400-watt BLDC motor load. The linear equation has an intercept value of -1.36766 and a slope value of 0.04791 for the Lead-acid battery. In contrast, the linear equation has an intercept value of -2.47064 and a slope value of 0.05417 for Lithium ion batteries. The average voltage drop across lead acid is 25% higher than that across Lithium-ion